Reason, Spirit and the Sacral in the New Enlightenment Islamic Metaphysics Revived and Recent Phenomenology of Life - Tymieniecka, A-T.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2011)
Rationality in its various expressions and innumerable applications sustains understanding and our sense of reality. It is traditionally differentiated according to its sources in the soul: in consciousness, in reason, in experience, and in elevation. Such a functional approach, however, leaves us searching for the common foundation harmonizing these rationalities. The perennial quest to resolve the aporias of rationality is finding in contemporary science$1 (Bs focus on origins, on the generative roots of reality, tantalizing hints as to how this may be accomplished. This project is enhanced by the wave of recent phenomenology/ontopoiesis of life, which reveals the workings of the logos at the root of beingness and all rationality, whereby we gaze upon the prospect of a New Enlightenment. In the rays of this vision the revival of the intuitions of classical Islamic metaphysics, particularly intuition of the continuity of beingness in the gradations of life, receive fresh confirmation.s
INTRODUCTION: REASON, SPIRIT AND THE SACRAL IN THE NEW ENLIGHTENMENT, Anna-Teresa Tymieniecka -- SECTION ONE: REASON, INTELLECT, AND CONSCIOUSNESS IN ISLAMIC THOUGHT, William C. Chittick, DIFFERENTIATION OF THE LOGOS: FROM REASON TO SACRAL SPIRIT IN THE ONTOPOIESIS OF LIFE, Daniela Verducci, ON THE HARMONY OF SPIRITUALITY AND RATIONALITY ACCORDING TO THE OPUS FASABIL IIWAN AO-NAFAB, Detlev Quintern -- SECTION TWO: REASON AND SPIRIT, Seyyed Mohammed Khamenei, LOGOS DIFFERENTIATING REASON AND SPIRIT IN PHENOMENOLOGY OF ANNA-TERESA TYMIENIECKA, Kathleen Haney, SPIRITUAL PARADIGM AS ORIGIN OF THE LIFE$1 (BS CAPACITY IN THE SADRAIAN PHILOSOPHY, Hossain Kalbasi Ashtari -- SECTION THREE: REASON AND SPIRIT IN THE THOUGHT OF EDMUND HUSSERL, ST. THOMAS AQUINAS, AND A-T. TYMIENIECKA, Thomas Ryba, REASON AND SPIRIT IN AL-BRUNI$1 (BS PHILOSOPHY OF MATHEMATICS, A.L. Samian, REASON AND SPIRIT, Mohammad Khajavi -- SECTION FOUR: THE DEBATE ABOUT GOD$1 (BS SIMPLICITY: REASON AND SPIRIT IN THE EIGHTH DISCUSSION OF AL-GHAZALI$1 (BS TAHAFUT AL-FALASIFA AND IBN RUSHD$1 (BS TAHAFUT AT-TAHAFUT, Ilona Kock, DIALECTICS ON REASON AND SPIRIT: RATIONAL DISCOURSES AND SPIRITUAL INSPIRATIONS, Nader El-Bizri, THE MYSTICAL POETRY OF SHIBLI, Kenneth Avery -- Index of Names.s
Keywords: Philosophy (General).; Ethics; Metaphysics; Philosophy, modern; Philosophy; Philosophy; Philosophy; Non-Western Philosophy; Metaphysics; Philosophy of Religion; Ethics